HUBUNGAN ENDORSER TERHADAP DAYA BELI KONSUMEN GREENLIGHT DI 3SECOND CLOTH SOLO GRAND MALL - NOVIARTA, FENSA (JURNAL KOMUNITAS, 2018)
The purpose of this research is to know the correlation between endoser to consumer appeal of Greenlight product in 3Second Cloth Solo Grand Mall. This research uses quantitative method with quantitative descriptive approach, using systematic scientific data to the parts and its relation. The object of this research is Greenlight consumers. Data collection techniques usedinterviews, observations and documentation. While the technique of data validitationis spearman’s coefficient rho rank- order correlation. The population in this study is Greenlight 3Second Solo Grand Mall Consumers. The sampling technique used in this study was random sampling with age, sex and occupational criteria. The analysis of shows that is correlation between consumer purchasing power and the role of endorser. This is indicated by Spearman’s Rho = 0,2787 coefficient value. Thus it can be concluded there is a correlation between consumer purchasing power with the role of endorser.